Novel divalent organo-lithium salts with high electrochemical and thermal stability for aqueous rechargeable Li-Ion batteries. (1st March 2019) - Ahmed, Faiz; Rahman, Md Mahbubur; Chandra Sutradhar, Sabuj; Lopa, Nasrin Siraj; Ryu, Taewook; Yoon, Soojin; Choi, Inhwan; Lee, Seungchan; Kim, Whangi
Abstract: Novel electrolytes with wide electrochemical potential window and high thermal stability have great potential for aqueous rechargeable lithium-ion batteries (ARLBs). Herein, we report the synthesis of two ionic salts of lithium sulfonylbis(fluorosulfonyl)imide (LiSFSI) and lithium carbonylbis(fluorosulfonyl)imide (LiCFSI) with divalent Li + for ARLBs. These ionic compounds are the derivatives of monovalent lithium bis(fluorosulfonyl)imide (LiFSI). The LiSFSI and LiCFSI exhibit the kinetic electrochemical stability window of ca. 3.78 and 3.52 V, respectively, which can be further expanded due to the formation of a stable solid electrolyte interface (SEI) layer. While LiFSI exhibits the kinetic electrochemical stability window of ca. 2.22 V without the formation of an SEI layer. Full ARLBs based on LiSFSI and LiCFSI electrolytes with a LiCoO2 cathode and graphite anode can deliver the specific discharge capacity of ca. 113.50 and 95.0 mAh/g, respectively, at 0.1C rate. Whereas, it is ca. 52.53 mAh/g for LiFSI at 0.1C rate. The capacity retention for LiSFSI, LiCFSI, and LiFSI based ARLBs are ca. 97.3, 89.6, and 67.8%, respectively, after 500 cycles. Furthermore, both LiSFSI and LiCFSI reveal much higher thermal stability compared to LiFSI. Thus, the derivatization of conventional ionic compounds is an effective strategy to enhance the battery performance and its lifetime. Graphical abstract: Highlights: Novel divalent organo-lithium electrolytes (LiSFSI and LiCFSI) were prepared and characterized. The electrolytes exhibited enhanced thermal and electrochemical stability. Both LiSFSI and LiCFSI have formed a stable and dense SEI layer. A maximum specific discharge capacity of 113.50 mAh/g was attained with LiSFSI in ARLBs.